(untitled) (Tokyo, 1992)
The result of a two-year study sponsored by CSIS and the Asia Pacific Association of Japan, this report offers an appraisal of ways to strengthen and stabilize the economic relationship between the United States and Japan at all levels - multilateral, bilateral and regional. A binational working group, co-chaired by former Under-Secretary of State William D. Rogers and former Ambassador to the United States from Japan Yoshio Okawara presents policy recommendations. Included are supporting papers on trade patterns, foreign direct investment and economic relations with China, Vietnam, Cambodia and Laos.
Keywords: Hoa Kỳ,Nhật Bản,United States,Japan,Japan; Quan hệ kinh tế đối ngoại,Quan hệ kinh tế đối ngoại,Foreign economic relations,Foreign economic relations,Foreign economic relations; Nhật Bản,Hoa Kỳ,Japan,United States,United States